A practical approach to the design of robust speed controllers for machine drives - Akpolat, ZH; Asher, GM; Clare, JC (Ieee-Inst Electrical Electronics Engineers Inc, 2000)
This paper presents a practical approach to the robust speed control of electrical drives. The approach is based on sliding mode control (SMC), but it is shown how sampling time, system noise, actuation limit, and antiwindup integrator reduce the control to an online maximum-gain selection constrained by system noise, The paper proposes a trajectory-reference compensator and fuzzy gain interpolator to fully exploit the system actuation while avoiding chattering and remaining within specified noise limits. Only the SMC switching line needs to be selected; the remaining control design is systematic and, thus, should be of interest to drive engineers in industry. Experimental results on a vector-controlled ac drive rig with variable-inertia loads are presented to verify the approach.
Keywords: adaptive control; motor drives; robustness; variable-structure systems